Outcome of Stromal Vascular Fraction-Enriched Fat Grafting Compared to Intramuscular Transposition in Painful End-Neuromas of Superficial Radial Nerve: Preliminary Results - Zimmermann, Simon; Fakin, Richard M.; Giovanoli, Pietro; Calcagni, Maurizio (Frontiers in Surgery, 2018)
Introduction: The management of painful end-neuromas of the superficial branch of the radial nerve (SBRN) remains challenging due to high levels of pain relapse. The novel technique of stromal vascular fraction (SVF)-enriched fat grafting showed continuous pain relief, although failed to prove statistically significant. Besides acting as a mechanical barrier, SVF-enriched fat grafting might also affect the cellular level. The aim of the study was to compare clinical outcomes of SVF to the widely popular intramuscular transposition technique. Patients and Methods: In this cohort study 10 consecutive patients treated for painful end-neuromas of the SBRN between 2010 and 2013 were analyzed retrospectively. Microsurgical resection of end-neuromas was performed in all patients. Five patients were treated with subsequent intramuscular transposition into the brachioradialis muscle and five patients received SVF-enriched fat grafting. Five different pain modalities and various predictors were compared pre- and up to 36 months postoperatively. Results: In the transposition group, sustained pain reduction was not observed after an initial significant reduction 2 months’ post-surgery, resulting in pain relapse at 36 months and comparable to the preoperative assessment. In the graft group, some degree of pain reduction was observed at 2 months after the surgery and proved to be constant in the long-term outcome, although not statistically significant compared to preoperative levels. Conclusion: Both SVF-enriched fat grafting and intramuscular transposition failed to prove statistical significant pain reduction in treating of symptomatic neuromas of peripheral nerves.